Filter-Feeding Bivalve Weakens Food Competition Between Crustaceans (Portunus trituberculatus, Marsupenaeus japonicus) in Integrated Culture Ponds: Evidence From 18S rDNA Barcoding and Stable Isotope Analysis - Xu, Xian; Dong, Shipeng; Zhang, Dongxu; Yu, Liye; Pu, Weijia; Xie, Yicheng; Shan, Hongwei; Wang, Fang (Frontiers in Marine Science, 2022)
In order to investigate the effects of razor clams (Sinonovacula constricta) on the food composition and isotopic niches of swimming crabs (Portunus trituberculatus) and kuruma shrimp (Marsupenaeus japonicus) in polyculture systems, this study quantified the food sources, food source contributions, and isotopic niches of cultured organisms using 18S rDNA barcoding and stable isotope techniques. The results suggested food competition between P. trituberculatus and M. japonicus, and S. constricta can reduce the competition and isotopic niche overlap, improve the contribution of food sources such as phytoplankton. Razor clams also serve to purify the water and improve the utilization of iced trash fish by filtering phytoplankton (51.10%), POM (32.25%), SOM (7.47%), and iced trash fish (9.18%). Thus, P. trituberculatus-M. japonicus-S. constricta is a healthy and sustainable culture model.